Necrostatin-1 Attenuates Cisplatin-Induced Nephrotoxicity Through Suppression of Apoptosis and Oxidative Stress and Retains Klotho Expression - Ning, Yichun; Shi, Yiqin; Chen, Jing; Song, Nana; Cai, Jieru; Fang, Yi; Yu, Xiaofang; Ji, Jun; Ding, Xiaoqiang (Frontiers in Pharmacology, 2018)
Purpose: Cisplatin is an effective chemotherapeutic drug, but the application in clinical is greatly limited by its nephrotoxicity. Necrostatin-1 (Nec-1), an inhibitor of RIP1 kinase, has been reported to inhibit RIP-mediated necroptosis. The aim of this study is to detect the protective effects of Nec-1 on the nephrotoxicity of cisplatin and to investigate its renoprotection mechanism. Methods: 8-week-old male C57BL/6 mice were randomly assigned into four groups: Control, Nec-1, Cisplatin, Cisplatin+Nec-1. Mice were treated with cisplatin with or without Nec-1 pre-treatment. Renal function, histological changes, necroptosis and apoptotic markers were investigated. NFκB pathway related proteins, proinflammatory cytokines, oxidative stress markers, renal Klotho and autophagy-related proteins levels were also examined. Results: Renal function and histological data displayed that the treatment with Nec-1 significantly attenuates cisplatin-induced renal damage. The expression of RIPK1/RIPK3/MLKL were significantly enhanced in cisplatin group as compared to the control group (p<0.05) and was significantly reduced by pre-treatment of Nec-1 (p<0.05). The level of stress and apoptosis-related protein, including p-JNK, p-c-Jun, p-p38, Bax/Bcl-2 ratio and caspase-3 showed the similar trend. Pre-treatment with Nec-1 inhibit NFκB signaling, reduced proinflammatory cytokines and oxidative stress, up-regulated renal Klotho and autophagy-related proteins levels. Conclusion: Our results suggest that Nec-1 could be a potential therapeutic drug against the cisplatin-induced nephrotoxicity through its anti-necroptosis, anti-apoptotic, anti-inflammatory, anti-oxidant and retain Klotho expression and activate autophagy effects in the kidney.